2021
DOI: 10.1016/j.jsps.2021.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among medical students at the Copperbelt University, Zambia: A cross-sectional study

Abstract: Background Self-medication is a common practice and cause for concern globally. There is a paucity of information regarding students’ self‑medication in Zambia. Therefore, this study aimed at determining the self‑medication practices among the medical students at Copperbelt University. Methods A descriptive cross-sectional study was conducted among 334 students. Data was collected using a semi-structured questionnaire, entered in excel, cleaned, and exported to SPSS ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
1
3
1
Order By: Relevance
“…The prevalence of SM found in our study is higher than the 61.1% that was reported in an earlier study among medical students at the Copperbelt University in Zambia (Banda et al, 2021), 76.8% in Nigeria (Asekun-Olarinmoye et al, 2019, 78% in Sri Lanka (Subashini & Udayanga, 2020), 71.7% in India (Ka-sulkar & Gupta, 2015), 64.98% in Ethiopia (Zewdie et al, 2020), 62.5% among University students in Iran (Delam et al, 2020), 54.3% in Portugal (Alves et al, 2021), 41% among pharmacy students in Zambia (Mudenda et al, 2022e), and14.5% in Peru (Rojas-Miliano et al, 2022). Our current findings indicate an increase in SM among university students during the COVID-19 pandemic compared to two earlier studies before that pandemic that reported a prevalence of 61.1% and 41% respectively (Banda et al, 2021;Mudenda et al, 2022e). Other studies also found a high prevalence of SM among university students, including 98.2% in Saudi Arabia (Alshammari et al, 2021), 95.4% in Nepal (Shah et al, 2021), and 83% in Pakistan (Yasmin et al, 2022).…”
Section: Discussioncontrasting
confidence: 87%
“…The prevalence of SM found in our study is higher than the 61.1% that was reported in an earlier study among medical students at the Copperbelt University in Zambia (Banda et al, 2021), 76.8% in Nigeria (Asekun-Olarinmoye et al, 2019, 78% in Sri Lanka (Subashini & Udayanga, 2020), 71.7% in India (Ka-sulkar & Gupta, 2015), 64.98% in Ethiopia (Zewdie et al, 2020), 62.5% among University students in Iran (Delam et al, 2020), 54.3% in Portugal (Alves et al, 2021), 41% among pharmacy students in Zambia (Mudenda et al, 2022e), and14.5% in Peru (Rojas-Miliano et al, 2022). Our current findings indicate an increase in SM among university students during the COVID-19 pandemic compared to two earlier studies before that pandemic that reported a prevalence of 61.1% and 41% respectively (Banda et al, 2021;Mudenda et al, 2022e). Other studies also found a high prevalence of SM among university students, including 98.2% in Saudi Arabia (Alshammari et al, 2021), 95.4% in Nepal (Shah et al, 2021), and 83% in Pakistan (Yasmin et al, 2022).…”
Section: Discussioncontrasting
confidence: 87%
“…This study showed that, 83.8% were practicing selfmedication during the last 1 year. Similar results were reported the SM in Medical Students especially during COVID-19 Pandemic: Lower rates were observed in studies conducted in Karachi (76%), Kolkata (65%), Iraq (68.73%), western Ethiopia (73.4%), Saudi Arabia (64.8%), Nigeria (69.4%) and Zambia (61.1%) 12,16,17,9,18,19 respectively. On the other hand, higher rates of SM among the university students were reported in studies conducted in Abbottabad (95.5%), Bangladesh (88%), Jordan (86.7%), Iran (94.1%), Saudi Arabia (98.7%) and Nepal (95.4%) 14,20,21,22 .…”
Section: Discussionsupporting
confidence: 85%
“…This prevalence is lower than that previously reported in a study from Pakistan, in which an online survey of 489 medical or pharmacy students showed that 83% of them practised self-medication during the COVID-19 pandemic [23]. A high prevalence of self-medication with the aim of maintaining health among medical students has been reported in studies in Indonesia (49%) [14] and other developing countries such as Nepal (80%) [8], Zambia (61%) [24], Serbia (80%) [7]and Iran (90%) [5].…”
Section: Discussionmentioning
confidence: 57%